O mito do herói nas obras O Gaúcho e O Sertanejo de José de Alencar - Freitas, Gabriele Freixeiras de (2015)
The objects of study in this dissertation are the aspects of the hero in the regionalist works O Sertanejo (1875) and O Gaúcho (1870), by José de Alencar. Through heroic characters, like Arnaldo and Manuel Canho, the writer from Ceará develops protagonists who represent the different regions of Brazil, thus basing his works on his project valuing the “local color” and the affirmation of a national identity. Guided by the aspects of the hero within the Romantic Movement, we will discuss some relevant features that can both differentiate and approach the characters to the heroes represented in other literary periods. To do so, we will draw a brief overview of the importance of the myth in archaic societies, as well as the origin and development of the mythologem of the hero. Through a detailed study of the hero from Alencar’s point of view, we intend to show how the author makes use of heroic aspects traditionally found in the Greek epopees and tragedies, strengthening the influence of the Homeric narrative in Western culture. However, the hero of the novel, as well as the own genre to which it belongs, has at its core the contradiction, the quest for the realization of their subjectivity in an objective world. Indeed, the hero, responsible for representing the novel, embodies the misfit in adapting to the society they live in and their inability to carry out the desires of the soul in a world unable to achieve them. This dissertation is based on the Works of Mircea Eliade (1972), Afrânio Coutinho (1995, 1999), Lukács (2000), Araripe Júnior (1980), among other researchers.